Two Cases of Acute Urinary Retention in Early Pregnancy: A Rare Obstetric Emergency - I Putu Adigama; Gede Indra Pratama (HM Publisher, 2025)
Acute urinary retention (AUR) is a rare but potentially serious complication in early pregnancy, characterized by the sudden inability to void, resulting in bladder distension and lower abdominal pain. The incidence of AUR in pregnancy is estimated to be around 1 in 3000 to 1 in 8000 pregnancies. While AUR can occur at any gestational age, it is most frequently encountered in the first and second trimesters. A retroverted uterus, where the uterus tilts backward instead of forward, is present in approximately 11-15% of women and is a major contributing factor to AUR. This case series presents two cases of AUR managed at our institution. The first case involved a 28-year-old woman, gravida 2, para 1, who presented at 14 weeks and 3 days gestation with continuous suprapubic pain and a sensation of incomplete bladder emptying. The second case involved a 38-year-old woman, gravida 6, para 3, who presented at 9 weeks and 2 days gestation with an inability to void since the previous night, along with suprapubic pain and a sensation of incomplete bladder emptying. Both women had a retroverted uterus on ultrasound. Successful management involved bladder decompression with a Foley catheter for 48 hours, followed by bladder training. In conclusion, AUR in early pregnancy necessitates prompt diagnosis and management to prevent maternal and fetal complications. A retroverted uterus is a significant risk factor. Catheterization and bladder training are effective in most cases.